Optimalisasi Kompetensi SDM serta Inovasi Produk dalam Kegiatan Pendampingan UMKM pada Usaha Makanan - Citra Anisa Tika Putri; Erin Soleha; Prasetyo Hari Sandi; Fahrurozi Muarief (Lembaga Pengembangan Kinerja Dosen, 2024)
The culinary world today has always been one of the favorite destinations of many people. Not only abroad, but there are many culinary tours in the country. No exception in Indonesia which has interesting culinary tourism locations to visit. The problems that occur are, the lack of understanding of MSME actors about the importance of digital or technological knowledge and literacy in MSME actors to improve quality human resources, the ineffectiveness of MSME programs in supporting business implementation strategies to increase MSME competitiveness, the lack of understanding of MSME actors in maintaining business sustainability through innovative creation to increase MSME added value. This Community Service activity of the Faculty of Economics and Business, Pelita Bangsa University will be carried out online and offline (hybrid), located at Perum Graha Kalimas 2 Blok C No. 20 Tambun, Bekasi Regency, West Java.